(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Values can be defined as broad preferences concerning appropriate courses of action or outcomes .As such, values reflect a person’s sense of right and wrong or what ‘ought’ to be. Values deal with what is good and bad, beautiful and ugly, normal and abnormal. Values are always collective within a group. Value denotes the degree of importance of something or action with the aim of determining what actions are best to do or what way is best to live. Religious values defined what people expect of themselves and of others based on the beliefs common to the religions they practice. Such values represent the core principles that guide daily decision making .They help people determine which actions to take ,and to make judgments about right or wrong and good or bad. Religious values are ethical principles founded in religious traditions, texts and beliefs. Religious values are based on scriptures and a religion’s established norms. Various aspects of the significance of religious values have been considered with respect to novels, their relevance to a particular religious group and in relation to human society. The world’s most commonly practiced religions often have similar values, although variations exist in the way some values are prioritized over others.